2005
DOI: 10.1002/adsc.200404266
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of (η5‐C5Me5)Hf(R)2[N(Et)C(Me)N(t‐Bu)] (R=Me and i‐Bu) for the Stereospecific Living and Degenerative Transfer Living Ziegler–Natta Polymerization of α‐Olefins

Abstract: (4b)], which were characterized in solution. Compounds 4a and 4b were evaluated as initiators for the stereospecific living Ziegler-Natta polymerization of 1-hexene. These results reveal that, while an extremely high level of stereoselectivity can be achieved to produce isotactic poly(1-hexene) in a living fashion, the rate constant for polymerization, k p , using either 4a or 4b, is~60 times less than that of the analogous zirconium initiators. Finally, upon substoichiometric activation of 3a with [PhNHMe 2 ]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 32 publications
(19 reference statements)
6
45
0
Order By: Relevance
“…The developmental activities of well‐defined transition metal catalysts capable of initiating stereospecific living propylene polymerization have been intense in the past three decades, because these catalysts may provide potentially high‐performance polymers such as monodisperse polypropylenes (PPs) with high melting temperatures ( T m s) and block copolymers containing high T m segment. Besides numerous catalysts capable of highly stereospecific polymerization of propylene,1–17 recent progress in the rational design of well‐defined catalysts for olefin polymerization has resulted in the discovery of a growing number of catalysts for living propylene polymerization 18–52. For example, biscyclopentadienyl metallocene,18 diamine bisphenolate zirconium complexes,19, 20 fluorinated bis(phenoxyketimine)titanium complexes,21–23 α‐diimine Ni(II)24 complexes, and monocyclopentadienyl zirconiumn complexes25 are able to catalyze propylene polymerization in a living manner.…”
Section: Introductionmentioning
confidence: 99%
“…The developmental activities of well‐defined transition metal catalysts capable of initiating stereospecific living propylene polymerization have been intense in the past three decades, because these catalysts may provide potentially high‐performance polymers such as monodisperse polypropylenes (PPs) with high melting temperatures ( T m s) and block copolymers containing high T m segment. Besides numerous catalysts capable of highly stereospecific polymerization of propylene,1–17 recent progress in the rational design of well‐defined catalysts for olefin polymerization has resulted in the discovery of a growing number of catalysts for living propylene polymerization 18–52. For example, biscyclopentadienyl metallocene,18 diamine bisphenolate zirconium complexes,19, 20 fluorinated bis(phenoxyketimine)titanium complexes,21–23 α‐diimine Ni(II)24 complexes, and monocyclopentadienyl zirconiumn complexes25 are able to catalyze propylene polymerization in a living manner.…”
Section: Introductionmentioning
confidence: 99%
“…Zr and Hf complexes with Cp * and the acetamidinate ligand (22, M = Zr, Hf, X = Me) promote isospecific living polymerization of hexene in the presence of stoichiometric amount of the borate cocatalyst (177)(178)(179)(180). Similar to the propylene polymerization catalyzed by the same catalysts, isotactic-atactic stereoblock polyolefin with the narrow molecular weight distribution can be synthesized by using the Zr catalyst via stepwise addition of the borate cocatalyst and the Zr complex (181).…”
Section: Stereospecific Polymerization Of Higher α-Olefinsmentioning
confidence: 99%
“…In all cases, the obtained molecular weights were five times higher than those predicted based on 126 www.chemcatchem.org the assumption of one chain per metal center (M theo n ), which indicates that approximately 20 % of the metal centers are active in the polymerization. [18,21,[40][41][42][43][44][45][46][47] We carried out a polymerization with [rac-Lig 1 HfBn 2 -b], which is cleanly synthesized upon initial metalation of 1 with [HfBn 4 ] (Figure 2), and obtained nearly identical polymerization results upon activation with BA C H T U N G T R E N N U N G (C 6 F 5 ) 3 at 0 8C as was obtained with [rac-Lig 1 HfBn 2 -a/b]/BA C H T U N G T R E N N U N G (C 6 F 5 ) 3 . Analysis of the polyA C H T U N G T R E N N U N G (1-hexene) microstructure by 13 C{ 1 H} NMR spectroscopy revealed that the polymer was regioregular and highly isotactic; the spectrum showed no signals corresponding to stereoerrors (Figure 7).…”
Section: -Hexene Polymerization Behaviormentioning
confidence: 99%